Locating and imaging contact delamination based on chaotic detection of nonlinear Lamb waves. (1st September 2018) - Liu, Xiaofeng; Bo, Lin; Yang, Kangjun; Liu, Yaolu; Zhao, Youxuan; Zhang, Jun; Hu, Ning; Deng, Mingxi
Highlights: The nonlinearity parameter is invalid under the noise interference. The chaotic detection is sensitive to the nonlinear harmonic and robust to the noise. The Lyapunov exponent is taken as the damage index to locate the delamination. The higher quality of delamination image can be achieved with Lyapunov exponent. Abstract: We propose a novel method for locating and imaging contact delaminations in composite plates, using a network of PZT transducers and the nonlinear Lamb waves. Being immune to noise and sensitive to weak signal, the Duffing chaotic oscillator is utilized to detect the nonlinear harmonics of Lamb waves generated at the contact delamination interfaces. The Lyapunov exponent of the Duffing system output is calculated to quantify the relative intensity of nonlinear second harmonic. Its normalized value is taken as the damage index to locate and image the delaminations by combining with the probabilistic imaging algorithm. The numerical simulation study on the proposed method is performed. Compared with the nonlinearity parameter and the conventional damage index, the Lyapunov damage index (LDI) can image the single delamination or multiple delaminations more effectively, especially under the noise interference. The experiment using the LDI is also conducted on a composite laminated plate with multiple internal delaminations. The results show that the proposed imaging method based on LDI is also valid to the practical delaminations in the composite plate. It has the following advantages: immunity to noise, needlessness of baseline data, high imaging resolution and location accuracy.